TRENDS FOR APPLICATION OF THE WEDGE AND RIBBED BELTS IN MODERN WOODWORKING MACHINЕRY (Innovation in Woodworking Industry and Engineering design, 2026)
The current paper makes an overview of trends in the use of V-belts and ribbed belts in modern woodworking machines. Driving of different types of mechanisms in machines is most often accomplished by using belt drives. They have many advantages and some of the most important are: simple construction, quiet operation, large towing capacity, the possibility of simultaneous operation of several belts and further more. Widely spreads are both the Vbelts and ribbed belts. Improved construction and use of high quality materials for their production leads to betterment their performance.